SUSTAINABILITY IN SERVICE´S SECTOR: NEW TRENDS OF SUSTAINABILITY TOOLS AND POSITIONING OF SERVICES IN ECONOMY - Johana Paluchová; Renata Prokeinová (Polityki Europejskie, Finanse i Marketing)
The goal of sustainable development is to meet the needs of the present without compromising the ability of future generations to meet their own needs. As economies globalize, new opportunities to generate prosperity and quality of life are arising though trade, knowledge-sharing, and access to technology. The article is a part of current scientific project at our department of marketing “VEGA No. 1/0951/12 Sustainability developments of subjects in the food chain at the condition of Slovak market.” In our article we like to introduce you a term of sustainability in service´s sector, such an ecological tourism at Slovak market through definition of sustainability and statistical methods used in prediction of chosen data such as GDP in service´s sector, service export and import and total prediction of Slovak service´s economy.